Components for Designing of Secure Routing Protocol - Zalte, SS; Ghorpade, VR (International Journal of Computer Sciences and Engineering, 2025)
In Mobile Ad-hoc Network(MANET) there are so many routing protocols are commenced. But no one will fulfill all security requirements. The crucial issue in MANET is Security due to the openness, infrastructure less and variable topology of MANET. In the broad dispersion of MANET, so many routing protocols are incorporated initially with the assumption that security must be retrofitted. Thus the routing protocols are more prone to various attacks with the risk of destruction of data. In this paper, we have discussed various components which will be required or helpful for designing of secure routing protocol in MANET.